Pengaruh Pengeluaran Pemerintah dan Investasi Terhadap Kesenjangan Pendapatan Dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening (Studi Empiris Pada Provinsi Se-Sumatera Tahun 2011-2014) - Ariza, Ifni, Drs. Atwal Arifin, Ak.,M.Si (2017)
Economic growth, investment allocation uneven and different levels of government spending will lead to inequality and income disparities public areas. This study aimed to analyze the effect of government spending and investment on the income gap with economic growth as an intervening variable in Sumatra province in 2011-2014. The population used in this study is the Sumatra province in 2011-2014. The sampling method with a purposive sampling. The number of samples collected as many as 36. With the data outliers by 2, then the sample was 34. In this study using path analysis. Before the path analysis has been performed classical assumption. The results showed that direct government expenditures have a significant effect on economic growth, while direct investment has no significant effect on economic growth. Furthermore, direct government spending no significant effect on the income gap, investment directly significant effect on income inequality, economic growth is directly no significant effect on the income gap, as well as government spending and investment significantly influence the income gap through economic growth. Keywords: government spending, investment, economic growth, income gap.